PENGARUH KONSENTRASI DOPING DAN FRAKSI MOL GERMANIUM PADA BASIS TRANSISTOR BIPOLAR HETEROJUNCTION SILIKON-GERMANIUM - Tjahjadi, Gunawan (Jurnal Teknik Elektro, 2001)
We present an analytical model of base and collector current distribution for SiGe HBT.This model covers some important factors to be well considered in the process of devicestructure fabrication: bandgap narrowing due to heavy doping and/or the addition ofgermanium fraction to silicon substrate, effective density of states at conduction and valenceband, and diffusion constant. Results have been made indicating the slightly different effectsbetween theoretical and experimental current distribution.Keywords: Heterojunction Bipolar Transistor /HBT, bandgap narrowing, effective densityof states